Comparison of intravenous paracetamol and caudal block in terms of analgesic effects in patients at pediatric surgery (Annals of Medical Research, 2021)
Aim: In our study, we aimed to evaluate retrospectively the efficacy of postoperative analgesia in patients with caudal block versus paracetamol in 67 cases, between the ages of 2-8 years who had undergone elective inguinal hernia and circumcision surgery after induction of general anesthesia.Material and Methods: In this study, we evaluated retrospectively the files of 67 cases between 2-8 years old patients who had caudal block or I.V. paracetamol who undergone inguinal hernia and circumcision operation between September 2017 and September 2018. The files of the cases, anesthesia follow-up forms and nurse observation forms were examined; demographic data, vital signs, duration of surgery, postoperative analgesic requirement and recorded complications were evaluated.Results: The mean age was 3.2±2.35 years in the caudal group and 4.3±2.15 years in the paracetamol group, the mean body weight was 15.1±4.51 kg in the caudal group and 19.4±6.4 in the paracetamol group. The surgical period of patients in the caudal group was 51±12.2 minutes and it was 37.8±15.8 in the paracetamol group. The mean duration of postoperative analgesia was 8.1±1.42 hours in the caudal group and 1.05±1.0 hours in the paracetamol group. There were no complications in any of the patients in the postoperative period. No significant results were found in the vital signs of both groups. While VAS values were statistically significant at 6th and 12th hours, VAS value at 24th hour was not statistically significant.Conclusion: Caudal epidural anesthesia may be a simple and safe method of anesthesia effective in postoperative pain control. May it ensure serious patient comfort with reduced analgesic requirements after surgery. It may be recommended to use pediatric surgery under umbilicus for high success rates and low complication rates.Keywords: Caudal block; analgesia; circumcision; inguinal hernia; paracetamol.
Keywords: Caudal block; analgesia; circumcision; inguinal hernia; paracetamol.